Changes in systemic cancer therapy in Australia during the Delta and Omicron waves of the COVID-19 pandemic (2021-2022): a controlled interrupted time series analysis - Forrest C Koch; Monica Tang; Ramesh Walpola; Maria Aslam; Sallie-Anne Pearson; Benjamin Daniels (Sax Institute, 2024)
Objectives: Australian lockdowns in response to the initial coronavirus disease 2019 (COVID-19) outbreak in 2020 were associated with small and transient changes in the use of systemic cancer therapy. We aimed to investigate the impacts of the longer and more restrictive lockdowns in the Australian states of New South Wales (NSW) and Victoria during both the Delta subvariant lockdowns in mid-2021 and the Omicron subvariant outbreak in late 2021/early 2022. Study type: Population-based, controlled interrupted time series analysis. Methods: We conducted a national observational study using de-identified records of government-subsidised cancer medicines dispensed to a random 10% sample of Australians between July 2018 and July 2022. We used controlled interrupted time series analysis to investigate changes in the dispensing, initiation and discontinuation of all cancer medicines dispensed to residents of NSW and Victoria, using the rest of Australia as a control series. We used quasi-Poisson regression to model weekly counts and estimate incidence rate ratios (IRRs) for the effect of (each) the Delta phase lockdown and the Omicron outbreak on our systemic cancer therapy outcomes. Results: Between July 2018 and July 2022, cancer medicines were dispensed 592 141 times to 33 198 people in NSW and Victoria. Overall, there were no changes to the rates of dispensing, initiation or discontinuation of antineoplastics during the Delta phase lockdowns. In both states during the Omicron outbreak, there were significant decreases in the dispensing of antineoplastics (NSW IRR 0.89; 95% confidence interval [CI] 0.84, 0.93. Victoria IRR 0.92; 95% CI 0.88, 0.96) and in the initiation of endocrine therapy (NSW IRR 0.85; 95% CI 0.74, 0.99. Victoria IRR 0.78; 95% CI 0.65, 0.94), and no changes in the discontinuation of any systemic cancer therapy. Conclusions: The 2021 lockdowns and 2021/2022 Omicron outbreaks in NSW and Victoria had significant impacts on the dispensing, initiation and discontinuation of systemic cancer therapies, however, the overall effects were minimal. The impacts of lockdowns were less significant than the Omicron outbreaks, suggesting COVID-19 infection, health system capacity, and patient and community concerns were important factors for treatment changes.